KOORDINASI KERJA RECEPTIONIST DENGAN ROOM ATTENDANT DI HOTEL TJOKRO PEKANBARU - Ramadhan, Nugraha; Ibrahim, Mariaty (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study aims to determine the work coordination and obstacles in the work practices of receptionists and room attendants at Hotel Tjokro Pekanbaru. The research method used is a qualitative method with data collection techniques through interviews and observations. The results of the study indicate that the work coordination between employees and reception staff with room attendants at Hotel Tjokro Pekanbaru has been running well, but there are still obstacles faced that have an impact on guest complaints and operational efficiency. Therefore, this study recommends improving the work coordination of receptionists and room attendants at Hotel Tjokro Pekanbaru through training and development as well as regular monitoring and evaluation so that reception staff and employees with room attendants at Hotel Tjokro Pekanbaru better understand work coordination and how to improve it. Keywords: Hotel, Coordination, Receptionist, Room Attendant.